Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Mitigating toxic trace metals contamination and CO2 emissions in soils and atmosphere through leachate treatment with coagulation and photocatalysis processes - Cherni Yasmin; Melki Samira; Louati Zeineb; Hechmi Sarra; Guedari Moncef; Trabelsi Ismail; Wahab Mohamed Ali (Euro-Mediterranean Journal for Environmental Integration, 2026)

Dual anti-inflammatory and immunomodulatory effects of clove essential oil and eugenol: targeting neutrophil functions and experimental arthritis - Othman El Faqer; Zaynab Ouadghiri; Hicham Wahnou; Ismail Elkoraichi; Abdelmoiz El Faqer; Asmae Mazti; Samira Rais; El Mostafa Mtairag (Inflammopharmacology, 2026)

Orogenic and fluvio-tectonic insights into the formation of the Middle Atlas Caves in the Jurassic dolomites (Morocco) - Iliass Naouadir; Samira Adil; El Hassane Chellai; Abdallah Elaaraj; Abdennabi Alitane; Mohammed Ettaki; Márton Veress; Ismail Naouadir (Proceedings of the Geologists' Association, 2025)

Pharmacological insights into Laurus nobilis: HPLC profiling and evaluation of its anti-Toxoplasma, antioxidant, and anti-hemolytic properties - Othman El Faqer; Ismail Elkoraichi; Mounia Latif; Françoise Debierre-Grockiego; Zaynab Ouadghiri; Samira Rais; Isabelle Dimier-Poisson; El Mostafa Mtairag (Biochemical Systematics and Ecology, 2024)

Effect of prolonged photoperiod on growth, gonadal development, sex ratio, and skin coloration of red tilapia (O. mossambicus × O. urolepis hornorum) - Hossam E. R. Sharaf; Samira S. Assem; Rania F. Ismail; Ashraf A. M. Zeitoun; Tarek M. A. Srour (Aquaculture International, 2024)
Farming of red tilapia is one promising direction in aquaculture. The objective of this study was to investigate the impact of long-day photoperiod on the growth performance, reproductive parameters, maturity, sex ratio, β-carotene content, and skin coloration of red tilapia. Early life larvae were allocated into three treatment groups in triplicates: T1 = control group (12L:12D), T2 = long-day group (18L:6D), and T3 = continuous illumination group (24L:0D) for 90 days. By the end of the experiment, gonadosomatic index (GSI), relative fecundity, steroid hormones, maturity stages, sex ratio, and ovarian and testicular histology were examined; also, growth performance, survival rate, skin color, and total β-carotene content were measured. The results indicated that GSI% and serum testosterone (T) in T3 group significantly increased with greater amount of spermatozoa of male fish. Also, growth parameters and HSI% in female fish displayed significantly increased for T3 group. Females in group T2 showed significant elevation in GSI%, relative fecundity, and estradiol (E2) with higher number of mature stage. Continuous light group (T3) showed shifted male sex ratio, while female percentage was higher in T2 group. The total β-carotene content of T3 group showed significant elevation with less number of black spots. This study demonstrated that continuous light manipulation during red tilapia early life could stimulate the growth and enhance coloration by reducing black spots that significantly affects economic profitability. Long-day application was effective in female reproductive performance and maturity. This study also served as an important reference for red tilapia aquaculture.

Performance improvement of polyethersulfone membranes with Ti3AlCN MAX phase in the treatment of organic and inorganic pollutants - Vahid Vatanpour; Seyed Ali Naziri Mehrabani; Ahmad Dehqan; Samira Arefi-Oskoui; Yasin Orooji; Alireza Khataee; Ismail Koyuncu (Chemosphere, 2024)

Multivariate Analysis and Correlation Study Shows the Impact of Anthropometric and Demographic Variables on Gut Microbiota in Obese Egyptian Children - Nada Mohamed Ezz El Deen; Mona Karem; Mervat Ismail El Borhamy; Amro Mohamed Said Hanora; Nora Fahmy; Samira Zakeer (Current Microbiology, 2024)

Phytochemical analysis and immunomodulatory activities in vitro and in vivo of Aframomum melegueta K Schum seed extracts - Mounia Latif; Ismail Elkoraichi; Othman El Faqer; Hicham Wahnou; El Mostafa Mtairag; Mounia Oudghiri; Samira Rais (Inflammopharmacology, 2024)

The effect of thyroxine (T4) and goitrogen on growth, liver, thyroid, and gonadal development of red tilapia (O. mossambicus × O. urolepis hornorum) - Rania F. Ismail; Samira S. Assem; Hossam E. R. Sharaf; Ashraf A. M. Zeitoun; Tarek M. A. Srour (Aquaculture International, 2024)
This study provides comprehensive results on the growth, thyroid, liver, and gonadal condition, maturity, and sex ratio in red tilapia exposed to exogenous thyroxine and goitrogen. One-gram red tilapia fingerlings were reared in three groups: control, thyroxine (T4) (10 nM), and goitrogen (sodium perchlorate, 30 mg/L) for 30 days, followed by 30 days without treatment. After the first 30 days of treatment, liver enzymes and whole-body T4 and T3 were assessed. The gonadosomatic index (GSI), maturity stages and sex ratio were examined. Final body weight (FBW), weight gain (WG), specific growth rate (SGR), and survival rate were also measured. Results revealed insignificant differences among groups in FBW, WG, SGR, and GSI, but the hepatosomatic index (HSI) of the goitrogen group significantly increased. Exogenous thyroxine significantly increased whole-body T4. Liver enzymes were not affected. Thyroid follicles of the thyroxine-treated fish showed large thyroid follicles, whereas the goitrogen-treated fish showed degenerated and negligible thyroid follicles. Liver tissue of the thyroxine-treated fish group displayed a few fat vacuoles, while perchlorate-treated fish showed hydrophobic degenerated hepatocytes. At the end of 60 days, the thyroxine treatment significantly increased FBW, WG, SGR, female GSI, and male hepatosomatic index (HSI). Perchlorate and thyroxine exposure, respectively, skewed sex ratios toward males and females. Exogenous T4 enhanced the maturity stages of both females and males, while perchlorate exposure delayed their gonadal ripening. These results validated the significant role of T4 during early life of red tilapia as it could improve the growth and maturity, and affect its sex ratio, while T4 insufficiency could alter these factors.

Pea protein globulins: Does their relative ratio matter? - Holly Husband; Sungil Ferreira; Fan Bu; Samira Feyzi; Baraem P. Ismail (Food Hydrocolloids, 2024)

Investigation of novel cold atmospheric plasma sources and their impact on the structural and functional characteristics of pea protein - Fan Bu; Samira Feyzi; Gaurav Nayak; Qingqing Mao; V.S. Santosh K. Kondeti; Peter Bruggeman; Chi Chen; Baraem P. Ismail (Innovative Food Science & Emerging Technologies, 2023)

Phenomic and genomic approaches to studying the inhibition of multiresistant Salmonella enterica by microcin J25 - Laila Ben Said; Jean‐Guillaume Emond‐Rheault; Samira Soltani; Sofiane Telhig; Séverine Zirah; Sylvie Rebuffat; Moussa Sory Diarra; Lawrence Goodridge; Roger C. Levesque; Ismail Fliss (Environmental Microbiology, 2020)
Summary In livestock production, antibiotics are used to promote animal growth, control infections and thereby increase profitability. This practice has led to the emergence of multiresistant bacteria such as Salmonella , of which some serovars are disseminated in the environment. The objective of this study is to evaluate microcin J25 as an inhibitor of Salmonella enterica serovars of various origins including human, livestock and food. Among the 116 isolates tested, 37 (31.8%) were found resistant to at least one antibiotic, and 28 were multiresistant with 19 expressing the penta‐resistant phenotype ACSSuT. Microcin J25 inhibited all isolates, with minimal inhibitory concentration values ranging from 0.06 μg/ml (28.4 nM) to 400 μg/ml (189 μM). Interestingly, no cross‐resistance was found between microcin J25 and antibiotics. Multiple sequence alignments of genes encoding for the different proteins involved in the recognition and transport of microcin J25 showed that only ferric‐hydroxamate uptake is an essential determinant for susceptibility of S . enterica to microcin J25. Examination of Salmonella strains exposed to microcin J25 by transmission electronic microscopy showed for the first‐time involvement of a pore formation mechanism. Microcin J25 was a strong inhibitor of several multiresistant isolates of Salmonella and may have a great potential as an alternative to antibiotics.

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

Megalencephalic leukoencephalopathy with cysts in twelve Egyptian patients: novel mutations in MLC1 and HEPACAM and a founder effect - Ghada M. H. Abdel-Salam; Mohamed S. Abdel-Hamid; Samira I. Ismail; Heba Hosny; Tarek Omar; Laila Effat; Mona S. Aglan; Samia A. Temtamy; Maha S. Zaki (Metabolic Brain Disease, 2016)

Chromosome 7p disruptions in Silver Russell syndrome: delineating an imprinted candidate gene region. - David Monk; Louise Bentley; Megan Hitchins; Rachael Myler; Jill Clayton-Smith; Samira Ismail; Sue Price; Michael Preece; Philip Stanier; Gudrun Moore (Human Genetics, 2002)